International journal of African culture and idea (2014)
Ancient Rome and her peoples have been portrayed in written texts back, then and in modem times, as having a culture of institutionalized violence. They have been portrayed as brutal, belligerent and unforgiving people who enjoy violence with an obsession for causing pain and suffering on their victims. Marcus Anneus Lucanus, in his De Bello Civili, chronicles the role of the Roman leadership and the violent nature of Roman society as depicted in the civil war between Julius Caesar and Pompey that eventually led to the collapse of the Republic. Earlier works by scholars such as Fanthant, Johnson, Joyce and others, have focused basically on historical account of the horrors of the fratricidal war in ancient Rome and the role of these protagonists (Pompey, Caesar). Yet others, like Widows were concerned with the misdating or misreading of the textual data. This paper however, aims at examining the role played by the leadership and the violent nature of the Romans, through a philological analysis of the poetics of Lucan’s delineation of this culture of conflicts and violence in his De Bello Civili, to show possible convergences and divergences of this culture in the ancient and modem world. The paper contends that the culture of violence as shown in the activities of the leadership and the Roman people, was responsible for the devastating fratricidal civil war that led to the collapse of ancient Roman Empire. The article concludes that the culture of violence is not a peculiarity of the ancient Romans, but that given such parameters that arc consistent with the theories of criminology, modem societies could suffer similar fate.